2004
DOI: 10.1079/bjn20041218
|View full text |Cite
|
Sign up to set email alerts
|

Soyabean protein hydrolysate prevents the development of hypertension in spontaneously hypertensive rats

Abstract: The aim of the present study was to investigate the anti-hypertensive and angiotensin-converting enzyme (ACE) inhibition effects of soyabean protein hydrolysate in spontaneously hypertensive rats (SHR). Soyabean protein hydrolysate was prepared by peptic hydrolysis and was added into the feed of SHR (0 % for the S0 group, 0·5 % for the S1 group, and 1 % for the S2 group) for 12 weeks. Systolic blood pressure and mean blood pressure of the S1 (164·3 (SEM 4·7); 128·0 (SEM 5·0) mmHg) and S2 (156·8 (SEM 1·6); 120·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 33 publications
5
43
0
Order By: Relevance
“…Our previous studies found that soy protein may lower blood pressure and retard the loss of renal function in rats with chronic renal failure ( 9 ). In a spontaneously hypertensive rat model, we found that the hydrophilic portion of soy protein hydrolysate (SPH) retarded the development of hypertension by its ACE-inhibitory activity ( 10). Soy protein was also reported to have beneficial effects on the inflammatory and nutritional statuses in patients with end-stage renal failure (11).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies found that soy protein may lower blood pressure and retard the loss of renal function in rats with chronic renal failure ( 9 ). In a spontaneously hypertensive rat model, we found that the hydrophilic portion of soy protein hydrolysate (SPH) retarded the development of hypertension by its ACE-inhibitory activity ( 10). Soy protein was also reported to have beneficial effects on the inflammatory and nutritional statuses in patients with end-stage renal failure (11).…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study showed that many different peptides with ACE inhibitory activities were produced after pepsin-pancreatin digestion ( 19 ). Our previous studies also showed that SPH inhibited ACE activity in spontaneously hypertensive rats ( 9 ). Separation of the hydrophilic hydrolysate from peptic-digested soy protein afforded some ACE inhibitory peptides, including Ile-Ala, Tyr-Leu-AlaGly-Asn-Gln, Phe-Phe-Leu, Ile-Tyr-Leu-Leu, and Val-MetAsp-Lys-Pro-Gln-Gly ( 20 ).…”
Section: Discussionmentioning
confidence: 92%
“…In a spontaneously hypertensive rat model, we found that the ACE inhibitory activity of the hydrophilic portion of soy protein hydrolysate (SPH) retarded the development of hypertension ( 9 ). Soy protein was also reported to have beneficial effects on inflammation and on the nutritional status of patients with end-stage renal failure ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18] Many ACE inhibitory peptides have been isolated from the thermolysin (TLN) hydrolysate of dried bonito, 9,19,20) sesame, 7) and soy bean protein. 10) In particular, supplements containing dried bonito peptide LKPNM (IC 50 ¼ 17 mM) and sesame peptide LVY (IC 50 ¼ 1:8 mM) are commercially available in Japan.…”
mentioning
confidence: 99%